Project-Based Inquiry (PBI) Global during a Pandemic: A New Learning Ecology Perspective - Marie P. Himes; Hiller A. Spires; Erin E. Krupa; Margaret L. Borden; Jessica L. Eagle (MDPI AG, 2023)
Building on new learning ecology theory and situated in the COVID-19 pandemic context, a qualitative research design was used to examine student and teacher perspectives on Project-Based Inquiry (PBI) Global. Drawing on Problem-Based Learning (PBL) and Project-Based Learning (PjBL), PBI Global supports participants toward engaging in inquiry-to-action aligned with the UN Sustainable Development Goals (SDGs). Data sources for this study included transcripts from student and teacher focus groups conducted before, during, and after the PBI Global process. Three themes emerged (1) creating global awareness of water issues, (2) learning to collaborate in remote and hybrid contexts, and (3) enhancing self-efficacy through iterative learning. The discussion focuses on the affordances and challenges of engaging in PBL during non-voluntary online learning, as well as study limitations and directions for future research.